Regulatory Disharmony In Mining Downstream Policies: Ensuring Investment Certainty And Environmental Protection In Indonesia - Arya Elang Anom; Zulfikri Toguan; Azbi Arief Habibi (CV. AFDIFAL MAJU BERKAH, 2026)
Indonesia's mining downstream (hilirisasi) policy, grounded in Law Number 3 of 2020 on Mineral and Coal Mining and Law Number 11 of 2020 on Job Creation, faces serious challenges stemming from regulatory disharmony that threatens investment certainty and weakens environmental protection. This study aims to analyze three main dimensions of such disharmony: first, the normative conflict between centralization of mining authority and regional government authority under Law No. 23 of 2014; second, the